Impact of leadership styles on employees’ turnover intentions with work stress and job dissatisfaction as moderator among building construction project in Selangor - Nur Syafiqa Nabila, Muhamad Amin (2023)
Leadership styles have a different impact on individuals, especially on employees. Job satisfaction and pressure were a few factors that contributed to drastic turnover intentions. The ignorance of employee’s well-being among leaders within the industry often leads to higher turnover intentions, failure in organizational management and coupled with error in generalizing past researchers on how different leadership style influence turnover intentions within the construction firms. High job stress and job dissatisfaction may lead to high turnover intention in the construction industry, high turnover intention may cause few of organizational damage and will increase the cost which will need to cover the cost related to recruiting and replacing lost talent, performance verification and training along with other direct and indirect costs. Few studies examined the impact of leadership styles on employees' propensity to leave their jobs. In other words, there hasn't been enough study done to confirm the relationship between them. Hence, the needs for further investigation on the sequel of different leadership on turnover intention among construction firms. This report will take on an approach of mixed method research. A causal-comparative quantitative study with cross-sectional survey of 125 questionnaires will be administered to respondents from G7 construction firms within Selangor. The Smart-PLS-Sem software will be used in analyzing the data. Followed by semi-structured interview session with selected 3 respondents for a deeper understanding on this study and adds more support to the quantitative data gathered. At the end of the analysis, this report will serve as proof for the relationship as there will be a positive significant link between leadership and turnover intention among employees as job stress and job dissatisfaction act as moderators. Likewise, will serve the perspective of leaders in regard to the topic. Thus, the expected result will add findings along with other studies particularly in construction firms.